Positive impact of autophagy in human breast cancer cells on local immunosurveillance. (2nd June 2016) - Ladoire, Sylvain; Enot, David; Senovilla, Laura; Chaix, Marie; Zitvogel, Laurence; Kroemer, Guido
ABSTRACT: In human breast cancer cells, the presence of cytoplasmic dots positive for microtubule-associated proteins 1A/1B light chain 3B (LC3B) indicates enhanced autophagic flux and favorable prognosis. LC3B + puncta within malignant cells positively correlate with the intratumoral abundance of CD8 + cytotoxic T lymphocytes, yet negatively correlate with the frequency of local FOXP3 + regulatory T cells and CD68 + tumor-associated macrophages, resulting in an improvement of CD8 + /FOXP + or CD8 + /CD68 + ratios.